Thermal and microwave dielectric properties of Li–Si-based ceramics. Issue 12 (15th June 2021) - Wang, Mingxia; Zhong, Chaowei; Yang, Zhengyi; Yang, Hongyu; Cao, Lei; Qin, Tianying; Zhang, Shuren
Abstract: This paper investigates thermal conduction, thermal expansion and microwave dielectric properties of Lix Si(0.50x 0.65x) O(1.5x 1.8x) (LS-based) ceramics. All samples were synthesized via the traditional solid-state reaction route. The mole ratio of Si 4+ /Li + ranges from 0.50 to 0.65. According to the results, the composite of Si 4+ /Li + = 0.55 showed high thermal conductivity of 8.325 W/(mK) and an average coefficient of thermal expansion of 8.401 × 10 −6 /K (at the temperature between 100 °C to 150 °C). In order to enhance the thermal properties, 4 wt% Al2 O3 is added to the LS-based ceramics and the most excellent thermal properties were obtained on the sample with the mole ratio of Si 4+ /Li + = 0.55, exhibiting the properties of the highest thermal conductivity of 11.836 W/(mK), an average coefficient of thermal expansion of 10.748 × 10 −6 /K (at the temperature between 100 °C to 150 °C), the lower dielectric constant of 6.32, excellent flexural strength of 194 MPa, and the optimum Q × f of 4565 GHz. In the present study, a new type of LS-based ceramics suitable for the transition layer of circuit board was developed. The doping of the Al2 O3 into the LS-based ceramics can significantly improve its thermal conductivity, adjust the coefficient of thermal expansion and promote the start-temperature of crystallization to a lower direction.